Effect of Vapor‐phase‐treatment to CuZnZr Catalyst on the Reaction Behaviors in CO2 Hydrogenation into Methanol. Issue 5 (5th February 2019) - Chen, Shuyao; Zhang, Junfeng; Wang, Peng; Wang, Xiaoxing; Song, Faen; Bai, Yunxing; Zhang, Meng; Wu, Yingquan; Xie, Hongjuan; Tan, Yisheng
Abstract: CuZnZr catalysts prepared by co‐precipitation method were treated by vapor‐phase‐treatment (VPT) method, and used for the synthesis of methanol for CO2 hydrogenation. Compared with conventional co‐precipitation method, this VPT with TPABr (TPABr: tetrapropylammonium bromide) induces obvious increases in the particles size of CuO, ZnO and ZrO2, promotes the formation of the rod‐like structure, Zn and Zr enrichments on surface and the presence of more concentration of oxygen vacancies. Due to the increases of particle size especially for CuO particles, the activity of the catalyst for CO2 hydrogenation to CO (RWGS reaction) is furthest suppressed, leading to dramatical decrease in conversion of CO2 . However, methanol productivity is affected relatively modestly due to the enrichments of Zn and Zr as another active species on the catalyst surface. In addition, catalyst properties and methanol selectivity can be regulated through adjusting the processing time. The catalyst with the processing time of 3 day (CuZnZr‐TPABr‐3d catalyst) shows a methanol selectivity above 90 % and no obvious deactivation appeared in a period of 100 h reaction. Abstract : Off your rocker : Vapor‐phase‐treatment with TPABr promoted the formation of the rod‐like structure, Zn and Zr enrichment on surface and the presence of more concentration of oxygen vacancies on CuZnZr catalyst, suppressing RWGS reaction. CuZnZr‐TPABr catalyst shows a methanol selectivity above 90 %. (TPABr: tetrapropylammonium bromide, RWGS: reverse water‐gas shift)